Experimental response of masonry walls in-plane loading strengthened with GFRP strips. (1st March 2020) - Capozucca, R.; Magagnini, E.
Abstract: In Italian seismic areas brickwork or stone masonry walls are commonly present in historic buildings. In recent years, the strengthening of masonry walls with external bonded (EB) fibre reinforced polymers (FRPs) has been increased to improve the tensile capacity of masonry that is normally weak. Many aspects of this strengthening method are not yet completely known; in particular, the debonding mechanisms of FRP strips need to be analysed through more investigation. The objectives have been, on one side, to investigate the behaviour of single-story shear brickwalls under in-plane loading with and without strengthening by Glass-FRP strips and, on the other hand, to analyze the mechanisms of debonding. Two experimental walls, built with historic solid clay bricks in scale 1/3rd, were subjected to precompression to simulate actual loading condition in masonry building for service loads and tested under cyclic shear force. One was strengthened after damage with EB GFRP strips - and then once again - subjected to the same loading until failure; another one was strengthened with GFRP strips without damage and subjected to the same path of loading until failure. The response of both models are presented and compared; finally, failure mechanisms are discussed.